Casa abrigo: acolhimento e suporte às mulheres vítimas de violência em Porto Nacional–TO - Silva, Maria Caroline de Oliveira (Universidade Federal do Tocantins, 2020)
Due to various mobilizations of women's groups fighting to combat violence against women, including domestic, family, sexual violence, femicide, gender violence, among others, the issue is gaining visibility, but still needs to be addressed. more places that welcome these women. For this reason, the objective of this work is to elaborate a proposal of architectural project to shelter women victims of any type of violence in the historical center of Porto Nacional, entitled as Casa Zoe. For this, it was made a theoretical survey about the theme violence against women, historical patrimony and historical center, because it is a preliminary project where the proposal is to revitalize a tumbled house of National port. The architectural proposal intends to design a house that provides quality service to vulnerable women.